A conceptual and practical approach to haemostasis in paediatric liver disease. Issue 9 (24th March 2016) - Magnusson, Maria; Ignjatovic, Vera; Hardikar, Winita; Monagle, Paul
Abstract : Children with liver disease can develop severe bleeding episodes and thrombosis. Liver failure usually results in decreased levels of procoagulant and anticoagulant factors. Additional risk factors, including changes in vascular flow and endothelial function, are of importance for the development of bleeding or thrombosis in individual vascular beds. Detailed studies of haemostatic disturbances in the setting of paediatric liver disease are sparse and extrapolation from adult studies is common. The spectrum of liver diseases and the haemostatic system differs between children and adults. Specific paediatric liver diseases are reported to have more distinctive effects on haemostasis and the risk of bleeding and/or thrombosis. Conclusion: we propose a model regarding haemostasis in paediatric liver disease, taking into account a number of specific variables and mechanisms, as well as the type of liver disease, which will provide a framework for clinical decision-making in these complex patients.